2018
DOI: 10.1007/s13197-018-3164-4
|View full text |Cite
|
Sign up to set email alerts
|

Combined postharvest UV-C and 1-methylcyclopropene (1-MCP) treatment, followed by storage continuously in low level of ethylene atmosphere improves the quality of Tahitian limes

Abstract: The green Tahitian limes () were exposed to 7.2 kJ m UV-C and 0.5 μL L 1-methylcyclopropene (1-MCP) treatments both separately and in combination. After treatment, fruit were stored in ethylene free (i.e. air containing < 0.005 μL L) or 0.1 μL L ethylene at 20 °C and 100% RH. The results showed that UV-C treatment delayed skin degreening and reduced endogenous ethylene production compared to untreated control fruit, however these effects reduced over the storage time. As expected, 1-MCP inhibited ethylene prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
2
5
1
Order By: Relevance
“…However, there was a significant difference in weight loss between the two ethylene storage conditions, where fruits stored at 0.1 µL L −1 ethylene (20 • C and 100% RH) had significantly greater weight loss compared to those fruits stored in air. This result is contradictory to those previously reported by Pristijono et al [17] who observed that there was no significant difference in weight loss when lime fruit were stored at both air and 0.1 µL L −1 ethylene following UV-C treatments. In this study, the differences in fruit weight loss between air and 0.1 µL L −1 ethylene storage atmospheres may be due to the higher respiration rate of fruits stored at 0.1 µL L −1 ethylene (as discussed in Section 3.6).…”
Section: Weight Losscontrasting
confidence: 99%
See 1 more Smart Citation
“…However, there was a significant difference in weight loss between the two ethylene storage conditions, where fruits stored at 0.1 µL L −1 ethylene (20 • C and 100% RH) had significantly greater weight loss compared to those fruits stored in air. This result is contradictory to those previously reported by Pristijono et al [17] who observed that there was no significant difference in weight loss when lime fruit were stored at both air and 0.1 µL L −1 ethylene following UV-C treatments. In this study, the differences in fruit weight loss between air and 0.1 µL L −1 ethylene storage atmospheres may be due to the higher respiration rate of fruits stored at 0.1 µL L −1 ethylene (as discussed in Section 3.6).…”
Section: Weight Losscontrasting
confidence: 99%
“…Over the past two decades, UV-C treatment (180-280 nm) has been evaluated as a postharvest treatment for fresh fruits and vegetables [8] including to reduce pathogen growth [9]. UV-C treatment has been reported to delay the ripening and senescence of apples [10], tomato [11,12], oranges [13], table grapes [14], mango [15], peaches [16] and limes [17]. Therefore, postharvest UV-C treatment has the potential to become a low cost, low technology treatment for reducing fruit and vegetable loss in the supply chain.…”
Section: Introductionmentioning
confidence: 99%
“…Higher ethylene production rates in the untreated control fruits were associated with senescence resulting in more rapid deterioration of physical characteristics and visual assessment of skin colour (color meter) turned low Hue values indicative of severe degreening at 10°C. The suppression of endogenous ethylene production in UV-C treated lime fruit has also been reported in peaches (Stevens et al 1998), tomatoes (Bu et al 2013) and lime fruit (Pristijono et al 2018a). This result suggests that suppression of endogenous production may be a mechanism of UV-C treatment in delaying lime fruit senescence.…”
Section: Ethylene Productionsupporting
confidence: 60%
“…Ultraviolet-C (UV-C) (180-280 nm) irradiation has been reported to have beneficial effect on maintaining postharvest quality of horticultural produce. For example, UV-C irradiation has been shown to delay degreening of broccoli (Buchert et al 2011), spinach (Artés-Hernández et al 2009) and limes during storage (Pristijono et al 2018a). In addition, UV-C irradiation treatment has been reported to reduce pathogen growth (Guerrero-Beltrán and Barbosa-Cánovas 2004) and decay in capsicums (Mercier et al 2001) and also to delay ripening and senescence in oranges (D'hallewin et al 1999), grapefruit (D'Hallewin et al 2000), tomatoes (Tiecher et al 2013), potatoes (Pristijono et al 2018b) and mangoes (Pristijono et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…During storage, senescence and decay of the 1-MCP-treated figs were lower than the untreated fruits [13]. Moreover, 1-MCP is often combined with other preservation methods, such as UV-C irradiation [14], calcium chloride [15], and methyl jasmonate [16], to extend the storage period of fruits.…”
Section: Introductionmentioning
confidence: 99%